Intertwined geometries in collective modes of two-dimensional Dirac fermions - Ankan Biswas; Avraham Klein (Physical Review Research)
It is well known that the time-dependent response of a correlated system can be inferred from its spectral correlation functions. As a textbook example, the zero-sound collective modes of a Fermi liquid appear as poles of its particle-hole susceptibilities. However, the Fermi liquid’s interactions endow these response functions with a complex analytic structure, so that this time-frequency relationship is no longer straightforward. We study how the geometry of this structure is modified by a nontrivial band geometry, via a calculation of the zero-sound spectrum of a Dirac cone in two dimensions. We find that the chiral wave functions, which encode the band geometry, fundamentally change the analytic structure of the response functions, which encode its Riemannian geometry. As a result, isotropic interactions can give rise to a variety of unconventional zero-sound modes, which, due to the geometry of the functions in frequency space, can only be identified via time-resolved probes. These modes are absent in a conventional Fermi liquid with similar interactions, so that these modes can be used as a sensitive probe for the existence of Dirac points in a band structure.